Preparation and Characterization of Natural Rubber-, Polyethylene- And Natural Rubber/Polyethylene-Clay Nanocomposites - Abdullah, Mohd Aidil Adhha (2007)
The present research aims at studying the influence of organoclay on the properties of natural rubber (NR), low density polyethylene (LDPE) and NR/LDPE blend. Two types of clays, namely montmorillonite, (MMT) (cationic clay) and layered double hydroxide (LDH) (anionic clay) were used in this study. Secondly, to identify the influence of the organoclay on the thermal and mechanical properties effectively, a thoroughly investigation of the NR-clay and LDPE-clay single-phase and NR/LDPEclay blend were performed. These nanocomposites were evaluated by X-ray diffraction (XRD), transmission electron microscopy (TEM), thermogravimetric analysis (TGA) and mechanical properties. The organo-montmorillonite (OMMT) and organo-LDH (OLDH) samples were prepared via ion exchange reaction using organic surfactants; cetyltrimethylammonium (CTA), n-dodecyl trimethylammonium (DDT), protonated octadecylamines (ODA) and dodecylamines (DDA) as well as dodecylsulphate (DS). The characterization of organoclay were carried out by the Fourier Transform Infrared spectroscopy (FTIR) and the Carbon, Hydrogen, Nitrogen and Sulphur (CHNS) elemental analysis, Scanning Electron Microscopy (SEM) as well as Surface Area and Porosity Analysis (ASAP). The preparation of a NR nanocomposite may be accomplished either by solvent method or by melt-blending technique. However, the melt-blending technique was applied in this study which is the industrially preferred process. The expansion of the interlayer spacing of the clay indicates the formation of intercalated as well as exfoliated types of nanocomposites which supported by TEM images and XRD diffractograms. Both the tensile strength and the modulus of the nanocomposite increased while elongation at break decreased with the addition of the clay. The Dynamic Mechanical Analysis (DMA) of nanocomposites exhibited enhancement of the storage modulus indicated that the elastic responses of pure NR towards deformation were strongly influenced by the presence of nanodispersed nano-layered material. The thermogravimetric analysis that showed the presence of clay layers in NR matrix gave insignificant improvement in thermal stability of NR-clay nanocomposites. LDPE-clay nanocomposites were prepared by in-situ grafting-intercalating in melt. The organoclay was first modified with maleic anhydride (MAH). It was then blended with LDPE in melt. The grafting MAH onto LDPE chain favors the exfoliation and intercalation of the organoclay, hence resulting better dispersion of clay layers in the LDPE matrix. Tensile properties revealed that the tensile strength increased up to 3 parts per hundred polymer by weight (php) while elongation at break decreased with the addition of the clay. Enhancement in storage modulus observed were the characteristic of reinforcing fillers. Thermally stable LDPE-clay nanocomposites were obtained with the increase of the clay content at higher temperature ( 400 oC). Polymer blends with ratio 70/30 amount of LDPE and NR with N, N-mphenylenebismaleimide (HVA-2) as a compatibilizer was developed. The introduction of cross-links into the elastomer phase has contributed to the improvement of the tensile properties of dynamically vulcanized LDPE/NR blends. These results are supported by scanning electron microscopy (SEM) and Atomic Force Microscopy (AFM) images of extracted surfaces of the blends. Finally, NR/LDPE-clay nanocomposites were successfully prepared by melt intercalation technique. XRD results revealed the formation of both intercalated and exfoliated nanocomposites. The tensile properties enhanced resulted from melt compounding of NR/LDPE with 3 php or less modified organoclay. All nanocomposites formed in this investigation showed enhancement in the mechanical properties which are the characteristic of reinforcing fillers. The TEM micrograph revealed the clay layers was dominantly distributed in NR domain and manifested by insignificant improvement in thermal stability of the nanocomposites.